If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3i = 6 + -1yi Reorder the terms: 3i + x = 6 + -1yi Solving 3i + x = 6 + -1iy Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add 'iy' to each side of the equation. 3i + iy + x = 6 + -1iy + iy Combine like terms: -1iy + iy = 0 3i + iy + x = 6 + 0 3i + iy + x = 6 Add '-1x' to each side of the equation. 3i + iy + x + -1x = 6 + -1x Combine like terms: x + -1x = 0 3i + iy + 0 = 6 + -1x 3i + iy = 6 + -1x Reorder the terms: -6 + 3i + iy + x = 6 + -1x + -6 + x Reorder the terms: -6 + 3i + iy + x = 6 + -6 + -1x + x Combine like terms: 6 + -6 = 0 -6 + 3i + iy + x = 0 + -1x + x -6 + 3i + iy + x = -1x + x Combine like terms: -1x + x = 0 -6 + 3i + iy + x = 0 The solution to this equation could not be determined.
| 45=25x | | x^2+22x-23= | | 9x+3(4x-8)= | | Y=-7/20x-7/3 | | 6w+3-2(-8w-1)=7(w-1) | | x^2+20x-21= | | r^5=12.5 | | 5-4ln(x)=6 | | [[b-3y]/[2b]]-[[6b-7y]/[2b]] | | b-3y/2b-6b-7y/2b | | (7*5.19615242271)-6.63324958071+9.94987437107-3.46410161514=x | | (7*5.19615242271)-6.63324958071+9.94987437107-3.46410161514= | | √72x^3/√x | | y(x^3-2)dx+(x^2-x)dy=0 | | Ys+yn=tfory | | 1/5s=1/5s-4 | | z^8-17z^4-16=0 | | A^2-11a=-24 | | [(4x^9)/y]^-3 | | 8n^2/2n | | t=0.106(50)+68.81 | | t=0.106(50)x+68.81 | | t=0.106x+68.81 | | 6n-(7+4n)= | | 9r^2s/5pq^3/3r^4s^2/20q^4 | | 8-9[4-(7y-3)]= | | 2/7(4) | | m(m+7)=78m^2 | | 2/6y=28 | | (6w-x-5)(4w-7x)=0 | | 7(m-5)=15(3-m)+2 | | 5u^2-10u=0 |